2015
DOI: 10.1016/j.stem.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Transcription of Distinct Classes of Endogenous Retroviral Elements Marks Specific Populations of Early Human Embryonic Cells

Abstract: About half of the human genome consists of highly repetitive elements, most of which are considered dispensable for human life. Here, we report that repetitive elements originating from endogenous retroviruses (ERVs) are systematically transcribed during human early embryogenesis in a stage-specific manner. Our analysis highlights that the long terminal repeats (LTRs) of ERVs provide the template for stage-specific transcription initiation, thereby generating hundreds of co-expressed, ERV-derived RNAs. Convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
335
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(351 citation statements)
references
References 37 publications
15
335
1
Order By: Relevance
“…An effect of HEMO in development should also be considered, taking into consideration that its expression is observed as early as at the eight-cell stage and persists at all of the subsequent embryonic stages. Of note, other ERVs-including HERV-H and HERV-K-have related profiles of expression, and abundant HERV-H RNA was recently shown to be a marker of cell "stemness" in humans and possibly play a role-via transcriptional effects and/or specific ERV-driven transcripts-in the maintenance of pluripotency in human stem cells (45)(46)(47)(48)(49) (reviewed in refs. [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…An effect of HEMO in development should also be considered, taking into consideration that its expression is observed as early as at the eight-cell stage and persists at all of the subsequent embryonic stages. Of note, other ERVs-including HERV-H and HERV-K-have related profiles of expression, and abundant HERV-H RNA was recently shown to be a marker of cell "stemness" in humans and possibly play a role-via transcriptional effects and/or specific ERV-driven transcripts-in the maintenance of pluripotency in human stem cells (45)(46)(47)(48)(49) (reviewed in refs. [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Retroelements can also contribute to embryonic stem cell (ESC) regulatory networks; many binding sites for pluripotency factors [such as Oct4 (Pou5f1) and Nanog] reside within primate-or human-specific ERVs in the human genome (Bourque et al, 2008). In addition, LTR elements are implicated in the regulation of specific genes in early embryogenesis (Bourque et al, 2008;Fort et al, 2014;Macfarlan et al, 2012;Peaston et al, 2004;Wang et al, 2014;Goke et al, 2015;Kunarso et al, 2010). TEs are also frequently bound by p53 (Trp53), with more than one-third of the genomic targets of this tumor suppressor overlapping with primatespecific ERVs (Wang et al, 2007), hence at locations not found for instance in the mouse genome.…”
Section: Transposable Elements and Their Impact On The Genomementioning
confidence: 99%
“…At sequences derived from TEs, this allows for the taming of transcriptional influences that would otherwise hamper early development, from zygotic genome activation to the establishment and normal differentiation of pluripotent stem cells (Rowe et al, 2010;Matsui et al, 2010;Rowe et al, 2013;Turelli et al, 2014;Macfarlan et al, 2012). KRAB-ZFPs display exquisitely regulated patterns of expression during the first few days of embryogenesis, both in humans and mice, mirroring the tightly orchestrated transcription of TEcontaining loci during this period Theunissen et al, 2016;Macfarlan et al, 2012;Fort et al, 2014;Gifford et al, 2013;Goke et al, 2015;Grow et al, 2015;Kunarso et al, 2010;Xue et al, 2013;Yan et al, 2013). The removal of KAP1 or its partner histone methyltransferase SETDB1 in murine or human ESCs activates the expression of multiple TEs (Matsui et al, 2010;Rowe et al, 2010;Turelli et al, 2014).…”
Section: Heterochromatin Induction In Early Development and Te Controlmentioning
confidence: 99%
“…27,31,71,72 These findings indicate that the transcriptional activities of the LTRs are correlated with and can be fine-tuned by the extents of LTR methylation. Thus, ERV-9 LTR retrotransposons, through differential methylation of CpGs may be able to differentially regulate transcription of the cis-linked genes to coordinate the transcription networks of human development and differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…1,2,28 Intergenic LTR retrotransposons have been reported to perform beneficial cellular functions in regulating the transcriptional network and pluripotency of the embryonic stem cells, potentially through synthesis of long, noncoding RNAs (lncRNAs) that are initiated by LTR enhancer and promoter from within the LTR. 27,[29][30][31] Indeed, over 80% of human lncRNAs contain retrotransposon sequences, among which the LTR sequences are represented disproportionately, 32 indicating prevalent transcriptional activities of the LTR retrotransposons, even though the LTRs are predominantly hypermethylated in the human genome. 33 To investigate the apparent paradox of hypermethylationmediated transcriptional silencing and widespread transcriptional activities of the LTR retrotransposons, we examined the DNA methylation status and the transcriptional activity of an intergenic ERV-9 LTR retrotransposon in the b-globin gene locus in human erythroid cells that transcribe high levels of globin genes.…”
Section: Introductionmentioning
confidence: 99%